Planting as an Environmental Conservation in Pulau Semut Nature Tourism Object, Pekanbaru: Penanaman sebagai Upaya Konservasi Lingkungan di Objek Wisata Alam Pulau Semut, Pekanbaru - Ikhsani, Hanifah; Eno Suwarno; Dodi Sukma RA; Eni Suhesti; Ambar Tri Ratnaningsih (Universitas Lancang Kuning, 2025)
As a coastal area, Pulau Semut Nature Tourism Object is susceptible to environmental degradation. Therefore, it is imperative to implement conservation strategies to preserve the surrounding ecosystem, guarantee the sustainability of ecotourism, and preserve the buffer zone. This activity aims to expand partner knowledge regarding coastal environmental conservation and the planting of fruit tree seeds. The activities carried out included socialization regarding planting and environmental conservation, the planting of fruit plant seeds, the provision of trash bins, and the evaluation of partners. Following the service, there was a 47% increase in partner knowledge of planting activities as an effort to conserve the coastal environment. Partners already demonstrated proficiency in planting trees, with a 100% survival rate for seedlings. The success of this planting can be attributed to the utilization of quality seeds, proper planting and maintenance techniques.